PERTUMBUHAN SETEK LADA SATU RUAS PADA BERBAGAI KOMPOSISI TANAH ALUVIAL DAN KOMPOS TANDAN KOSONG KELAPA SAWIT - Petrus Riki Purnama; Dini Anggorowati; Iman Suswanto (Jurnal Sains Pertanian Equator, 2019)
This study aims to obtain the composition of alluvial soil and oil palm empty fruit bunches (OPEFB) compost that provides the best growth of pepper cuttings. This research was conducted  in Parit Demang village, South Pontianak. This study  start from February 25th, 2018 to May 25th, 2018. This study used an experimental method with a Complete Randomized Design pattern (CRD) it’s a dose of OPEFB compost with 4 levels treatment, each treatment consists of 6 replication and consisting of 10 sample plants. The first treatment alluvial soil composition : OPEFB compost (1:0), second treatment alluvial soil composition : OPEFB (1:1), third treatment alluvial soil composition : OPFB compost (1:2) and fourth treatment alluvial soil composition : OPEFB compost (1:3). Variables observed is: percentage of live seed (%), shoots length (cm), number of shoots per plants (unit), number of  leaves (strand), roots volume (cm3), dry weight of shoots (gram) and dry weight of roots (gram). Based on the results of research on the composition of alluvial soil media: 1:2 OPEFB compost and alluvial soil media: 1:3 OPEFB compost gives the same good growth on pepper cuttings. The composition of alluvial soil media: 1:2 OPEFB compost is more effective because it does not require a lot of OPEFB compost so that it can be used in the pepper cutting nursery. Key Words : Alluvial Soil, OPEFB Compost, Pepper Cuttings One Segment